2018
DOI: 10.1038/s41598-018-31885-6
|View full text |Cite
|
Sign up to set email alerts
|

The Atlantic salmon (Salmo salar) antimicrobial peptide cathelicidin-2 is a molecular host-associated cue for the salmon louse (Lepeophtheirus salmonis)

Abstract: Chemical signals are a key element of host-parasite interactions. In marine ecosystems, obligate ectoparasites, such as sea lice, use chemical cues and other sensory signals to increase the probability of encountering a host and to identify appropriate hosts on which they depend to complete their life cycle. The chemical compounds that underlie host identification by the sea lice are not fully described or characterized. Here, we report a novel compound - the Atlantic salmon (Salmo salar) antimicrobial peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Núñez‐Acuña et al. (2018) recently showed that the antimicrobial peptide cathelicidin‐2 present in Atlantic salmon skin and mucus is a molecular host‐associated cue for the salmon louse L. salmonis, as it is detected by the parasite which can then modify its swimming behaviour. For instance, it could be of interest to study the effect of cortisol and/or stressing procedures on the production of this molecule in skin mucus to test our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Núñez‐Acuña et al. (2018) recently showed that the antimicrobial peptide cathelicidin‐2 present in Atlantic salmon skin and mucus is a molecular host‐associated cue for the salmon louse L. salmonis, as it is detected by the parasite which can then modify its swimming behaviour. For instance, it could be of interest to study the effect of cortisol and/or stressing procedures on the production of this molecule in skin mucus to test our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the infestation stage, copepodid attachment behaviour is triggered by a combination of visual, mechanosensory and chemosensory stimuli (Fields et al., 2018; Mordue & Birkett, 2009). Some of the semiochemicals released by the mucus of fish have already been demonstrated to be involved in host‐parasite interactions (Bailey et al., 2006; Delfosse & Pageat, 2014; Ingvarsdóttir et al., 2002; Mordue & Birkett, 2009; Núñez‐Acuña et al., 2018; Pageat & Delfosse, 2014; Pino‐Marambio et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Marine organisms are a very important source of antimicrobial agents (Richards et al, 2001;Schillaci et al, 2010;Schillaci et al, 2013;Spinello et al, 2018;Vazzana et al, 2018;Núñez Acuña et al, 2018) and, among them, the PUFAs are normally present at high levels in Salmo salar (Linder, Fanni & Parmentier, 2005;Morais et al, 2009). Different studies have shown the antimicrobial activity of the salmon PUFAs against Gram-positive bacteria due to their specific components such as eicosapentaenoic acid (Desbois, Mearns-Spragg & Smith, 2009;Desbois & Lawlor, 2013), docosahexaenoic acid (Coonrod, 1987;Feldlaufer et al, 1993;Gladyshev et al, 2009), γ-linolenic acid (Asthana et al, 2006) and dihomoγ-linolenic acid (Feldlaufer et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Host identification via detection of semiochemicals has also been reported 16 . In C. rogercresseyi, the presence of advanced chemoreceptors that are capable of identifying specific molecules of different host species has recently been described [17][18][19] . Herein, the gene family of ionotropic receptors (IRs) are pivotal molecular components for the salmon-louse interaction 20,21 .…”
Section: Background and Summarymentioning
confidence: 99%